2021
DOI: 10.14348/molcells.2021.0203
|View full text |Cite
|
Sign up to set email alerts
|

The Danger-Associated Peptide PEP1 Directs Cellular Reprogramming in the Arabidopsis Root Vascular System

Abstract: When perceiving microbe-associated molecular patterns (MAMPs) or plant-derived damage-associated molecular patterns (DAMPs), plants alter their root growth and development by displaying a reduction in the root length and the formation of root hairs and lateral roots. The exogenous application of a MAMP peptide, flg22, was shown to affect root growth by suppressing meristem activity. In addition to MAMPs, the DAMP peptide PEP1 suppresses root growth while also promoting root hair formation. However, the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Recent studies (Jing et al, 2019;Okada et al, 2021;Poncini et al, 2017) reported that root growth was impaired by perceiving biotic or abiotic stress signals. Consistent with this finding, we also identified that plant elicitor peptide 1 (PEP1), a general sensor of biotic and abiotic stresses, affects the reprograming of Arabidopsis root apical meristem and vascular development (Dhar et al, 2021). In addition, PEP1 strongly impacts the cell-to-cell symplastic connection, which is responsible for transporting developmental signals over a long distance.…”
Section: Securing Plant Defense Under High Temperatures Without Growt...supporting
confidence: 70%
“…Recent studies (Jing et al, 2019;Okada et al, 2021;Poncini et al, 2017) reported that root growth was impaired by perceiving biotic or abiotic stress signals. Consistent with this finding, we also identified that plant elicitor peptide 1 (PEP1), a general sensor of biotic and abiotic stresses, affects the reprograming of Arabidopsis root apical meristem and vascular development (Dhar et al, 2021). In addition, PEP1 strongly impacts the cell-to-cell symplastic connection, which is responsible for transporting developmental signals over a long distance.…”
Section: Securing Plant Defense Under High Temperatures Without Growt...supporting
confidence: 70%
“…However, estradiol-induced STZ-OE line #2 displayed a significant increase of "extra xylem" vessel differentiation as compared to the WT seedlings grown on 10 M estradiol plates (~15% in WT and ~30% in STZ-OE#2) (Figure 3i; S11c and d; Table S11). These STZ-OE phenotypes recapitulate the PEP1-influenced phenotypes of WT, supporting the crucial role of STZ in the PEP-mediated reprogramming of root development (Dhar et al, 2021).…”
Section: Stz Reprograms Root Meristem As Part Of the Pep1 Signaling C...supporting
confidence: 61%
“…Indeed, expressing a high dosage of STZ in the root meristem using an estradiol-inducible transactivation system (STZ-OE line #2) resulted in (i) the exhaustion of stem cell niche, (ii) an early and ectopic xylem vessel differentiation, and (iii) aberrant divisions in the QC. These phenotypes are reminiscent of those found in the seedlings treated with PEP1 (Jing et al, 2019;Dhar et al, 2021;Okada et al, 2021). The STZ-OE transgenic line #2 phenotypes are further supported in the RNA-seq analyses.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations